2013
DOI: 10.1186/1756-6614-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of lithium induced thyroid abnormalities: a current perspective

Abstract: BackgroundLithium is an integral drug used in the management of acute mania, unipolar and bipolar depression and prophylaxis of bipolar disorders. Thyroid abnormalities associated with treatment with lithium have been widely reported in medical literature to date. These include goitre, hypothyroidism, hyperthyroidism and autoimmune thyroiditis. This current review explores the varied thyroid abnormalities frequently encountered among patients on lithium therapy and their management, since lithium is still a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 37 publications
(53 reference statements)
6
75
0
7
Order By: Relevance
“…Increased thyroid volume on ultrasonography is an expected finding in patients who have been using lithium for a long time. 17,30,[34][35][36] Bauer et al reported that thyroid enlargement that cannot be detected by palpation may be detected with ultrasonography and they recommended regular ultrasonography examinations. 22 An association was not found between thyroid volumes and hypothyroidism in lithiumtreated bipolar patients in a study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased thyroid volume on ultrasonography is an expected finding in patients who have been using lithium for a long time. 17,30,[34][35][36] Bauer et al reported that thyroid enlargement that cannot be detected by palpation may be detected with ultrasonography and they recommended regular ultrasonography examinations. 22 An association was not found between thyroid volumes and hypothyroidism in lithiumtreated bipolar patients in a study.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium use is known to reduce synthesis and release of thyroid hormone. 30 Initial low fT3 and fT4 levels may be associated with lithium use in bipolar patients. fT4 level was found to be lower in lithium-treated bipolar patients compared to healthy controls in a study.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium salt also has similar depressive effects on thyroid function. 5 Diazepam reduces cortisol levels 6 , while chlorpromazine increases prolactin in body. 7 So, different amount of major hormones in the two genders leads to sex based different responses to certain drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive experience in clinical use of lithium in treatment of bipolar disoreder revealed that lithium can cause disorder in thyroid function [51,52]. The most common complication is a goiter, less often hypothyroidism.…”
Section: Abstract: Lithium Glycogen Synthase Kinase 3 β-Amylmentioning
confidence: 99%